Penanganan Konflik Ambon dalam Analisis Dialektics Peace-Reconciliation dari Bar- Siman-Tov - Shofiyah, St.; Cangara, Hafied (Institut Agama Islam Negeri Kendari, 2023)
Abstract The concept of conflict management often focuses only on how to stop the conflict. However, how to prevent these conflicts from happening again, and how to maintain permanent peace, often escapes scientific studies and the attention of conflict theorists and parties concerned with world peace. Based on this phenomenon, Bar-Siman-Tov developed a theory regarding the creation of lasting peace (stable peace) through a dialectic between the